DIAGNOSING DYING: WHEN WE MISS THE BOAT. Issue 2 (1st June 2013) - Corke, Charlie
Abstract : As good as Advance Care Planning (by both doctors and patients) may become we will still be confronted by the acutely deteriorating patient who will die without treatment—but might well have their death miserably prolonged by treatment. These decisions confront us on a daily basis. Good medicine requires doctors to assist patients to make good decisions (a decision ie, right for that patient at that time). This requires skills that are rarely taught but can be learned. The decision making process in a high risk situation (death vs suffering) is complex. The decision-making process requires two important components: an understanding of the natural history of the disease that the patient has (without undue optimism) an understanding of the person themselves (their values, wishes and fears). Balancing the person (with their values, wishes and fears) with the medical situation that they find themselves in often reveals a clear treatment choice. The thought process can help both the patient and the doctor arrive at a 'good' answer—and hopefully informs a shared decision. The 'When Enough-is-Enough' course teaches this concept in a straightforward way that empowers junior doctors to explore their patient's values. The concept is not new: In the early 1900s the great physician, Sir William Osler stated: "It is much more important to know what sort of a patient has a disease than what sort of a disease a patient has." His words are more pertinent today than ever.